Adaptive Governance in Immigration Inspection in the Era of Global Mobility - Dani Hidayat Lubis; Ulul Albab; Amirul Mustofa (International Forum of Researchers and Lecturers, 2026)
Increasing cross-border human mobility and evolving immigration policies require public organizations to maintain flexible management systems capable of balancing service delivery, regulatory oversight, and national security. This study aims to analyze the implementation of adaptive governance in immigration inspections at the Surabaya Class I Special Immigration Office (TPI) within the context of global mobility. Employing a qualitative approach and a case study design, the research gathered data through in-depth interviews, observation, and document analysis, utilizing an interactive model comprising data condensation, data display, and conclusion drawing. The findings reveal that adaptive governance is manifested in three key aspects. First, adaptive leadership and collaborative governance strengthen decision-making, organizational communication, and inter-agency coordination during immigration inspections. Second, service innovation and digitalizationachieved through the use of immigration information systems, data integration, and procedural simplification—enhance service efficiency and accuracy. Third, organizational adaptability is demonstrated by the capacity to respond to regulatory changes and rising international mobility, as well as through organizational learning and continuous employee competency development. The study concludes that successful immigration inspection relies not only on regulatory compliance but also on the organization's ability to establish a governance framework that is adaptive, collaborative, innovative, and technology-driven. Ultimately, the research proposes an adaptive governance model integrating adaptive leadership, inter-agency collaboration, digital transformation, and organizational learning as a foundation for improving the effectiveness of immigration inspections in the era of global mobility.